MASALAH AGENCY DALAM PEMBIAYAAN MUDHARABAH DI BANK SYARI’AH (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2014)
This paper attempts to theorise the behaviour of the Islamic firm in the light of the new theory of the firm. In this papers, we explore the agency problems and effort to minimalize the agency problems throught screening of adverse selection. The adverse selection due to the pre-contractual endowment of information to the entrepreneur about the productivity of the venture with respect to effort and capital. The agency problem will not happened in the mudharabah financing if the shahibul mal applied the restricted screening of adverse selection to the mudharib. The study has found that there are six attributes considered from the mudharabah projects point of view, which include the prospect of project, availability of collateral, healthiness of project, project’s financial statements, clarity of contract conditions, and conformity of time period. In regard to mudharib attributes, the study has also concluded five characteristics which are considered important. They include the business capacity, [personal] collateral, mudharibs’ reputation and family background, and their business commitments.Keywords: Screening, Adverse selection, Moral hazard, Agency problemTulisan ini mencoba untuk berteori perilaku perusahaan Islam dalam terang teori baru perusahaan. Dalam makalah ini, kami mengeksplorasi masalah keagenan dan usaha untuk meminimalkan masalah lembaga pikir screening seleksi yang merugikan. Pemilihan merugikan karena dana abadi pra-kontrak informasi kepada pengusaha mengenai produktivitas usaha sehubungan dengan usaha dan modal. Masalah keagenan tidak akan terjadi dalam pembiayaan mudharabah jika mal shahibul menerapkan skrining terbatas seleksi merugikan mudharib.Studi ini menemukan bahwa ada enam atribut yang dianggap dari proyek mudharabah sudut pandang, yang meliputi prospek proyek, ketersediaan jaminan, kesehatan proyek, laporan keuangan proyek, kejelasan kondisi kontrak, dan kesesuaian jangka waktu. Dalam hal atribut mudharib, studi ini juga telah menyimpulkan lima karakteristik yang dianggap penting. Mereka termasuk kapasitas bisnis, [pribadi] agunan, reputasi mudharibs 'dan latar belakang keluarga, dan komitmen bisnis mereka.Kata kunci: Penyaringan, seleksi Adverse, moral hazard, masalah Agency